Korelasi Kecerdasan Spiritual Terhadap Profesionalitas Pendidik di SMP Negeri 34 Samarinda - Mahnunah, Siti (LP2M IAIN Samarinda, 2020)
Spiritual intelligence is one aspect of intelligence in humans that determines a person's performance in his work, especially for an educator when the current education system becomes one of the activities affected by the co-19 pandemic, where spiritual intelligence becomes a benchmark in completing obligations and responsibilities as an educator. So this study aims to determine the correlation between spiritual intelligence with the professionalism of an educator in facing today's global challenges. This research is a Field Research that uses a quantitative approach, data obtained through observation, questionnaires, and documentation. The research variables are spiritual intelligence and professionalism of teachers, and to find out the correlation between the two variables, then using statistical data analysis in the form of Spearman correlation coefficient with a significance value of 5% of 0.025 through IBM SPSS 20. The result of the study is 0.756 with a significance value of 0, while based on the interpretation table states that the relationship between these two variables is high/strong and the significance value in the correlation is 0 which is smaller than 0.025, in other words these two variables have a very close relationship.